Industrial Revolution 4.0: The Role of Technology In Existence Mastery Business and Implementation - Putri, Nada Kustia Perdana (International Journal of Social Service and Research, 2023)
This research aims to analyze the extent of the role of technology in implementation business to development era Which the more demand modern acceleration of regeneration. The evolutionary rotation cycle that will continue to be treaded by public throughout circles can create innovations new Which influence on business development. Research methods conducted in This study uses descriptive qualitative methods from various reference sources. Population Which function strengthen argument in study This is a number of districts/cities in Indonesia that can be taken with a simple sample size random sampling. From results study simple random sampling the, revealed that the emergence of this revolution causes many things to change such as machine technology that replaces operational systems. And also the results of research from all explanations state (1) Various site in application technology digital give convenience For coordinating every input and output of business actors. (2) Existing businesses can be revived with technology in various fields. (3) All aspects related to technology will enter the realm of the speed economy.